we are given
![x^2y-2xy-24y=y(x^2-2x-24)](https://tex.z-dn.net/?f=x%5E2y-2xy-24y%3Dy%28x%5E2-2x-24%29)
now, we can factor out right side term
![x^2-2x-24=x^2-6x+4x-6*4](https://tex.z-dn.net/?f=x%5E2-2x-24%3Dx%5E2-6x%2B4x-6%2A4)
![x^2-2x-24=(x-6)(x+4)](https://tex.z-dn.net/?f=x%5E2-2x-24%3D%28x-6%29%28x%2B4%29)
now, we can plug back
and we get
so,
.............Answer
Answer:
128 men
Step-by-step explanation:
90 × 28 × 8 = M × 18 × 15/2
M = 128
(B)Decreasing is the answer
Hi,
Answer: 7/27
<u>My work:</u> For this problem is already simplified to its simplest terms.
I Hoped I Helped!
Answer:
D
Step-by-step explanation:
TS and QR Is your answer